2013
DOI: 10.1128/iai.01080-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Expression Analysis of Nonproliferating Intracellular Salmonella enterica Serovar Typhimurium Unravels an Acid pH-Dependent PhoP-PhoQ Response Essential for Dormancy

Abstract: Genome-wide expression analyses have provided clues on how Salmonella proliferates inside cultured macrophages and epithelial cells. However, in vivo studies show that Salmonella does not replicate massively within host cells, leaving the underlying mechanisms of such growth control largely undefined. In vitro infection models based on fibroblasts or dendritic cells reveal limited proliferation of the pathogen, but it is presently unknown whether these phenomena reflect events occurring in vivo. Fibroblasts ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
94
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 79 publications
(121 reference statements)
5
94
0
Order By: Relevance
“…The S. enterica serovar Typhimurium strain SV5015 used in this study, described in the fibroblast infection model, 18 is a His C derivative of the mouse virulent strain SL1344. 61 Derivative SV5015 strains were generated bearing plasmids pC.IGdsRed33 and pFPVmcherry 38 for constitutive production of fluorescent proteins DsRed and mCherry, respectively.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S. enterica serovar Typhimurium strain SV5015 used in this study, described in the fibroblast infection model, 18 is a His C derivative of the mouse virulent strain SL1344. 61 Derivative SV5015 strains were generated bearing plasmids pC.IGdsRed33 and pFPVmcherry 38 for constitutive production of fluorescent proteins DsRed and mCherry, respectively.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
“…15 S. Typhimurium displays similar limited growth capacity in cultured fibroblasts 16,17 and in vivo inside nonphagocytic stromal cells located in the intestinal lamina propria. 18 Conversely, S. Typhimurium proliferates actively following entry into cultured epithelial cells. 19 Most reports using cultured epithelial cell lines describe net increases in intracellular bacterial loads up to 30-to 40-fold.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that crosstalk between SPI-1 and SPI-2 could also occur in intracellular bacteria, although this aspect remains to be demonstrated. More recent studies have shown that intracellular bacteria express SPI-1 genes and protein effectors translocated by the TTSS encoded by this island (25)(26)(27)(28)(29). Representative examples are the SPI-1 effector proteins SopB and SipA.…”
mentioning
confidence: 99%
“…Thus, most of these bacteria remain in a nongrowing state, reaching an average progeny of 3 to 4 cells per infected fibroblast at late infection times (36). In vivo, the PhoP-PhoQ system was reported to attenuate growth of intracellular bacteria located in nonphagocytic stromal cells present in the lamina propria of the mouse intestine (29). Recently, bacteria located inside phagocytes present in mouse organs have been shown to reach high numbers in the absence of SPI-2 (37).…”
mentioning
confidence: 99%
“…11 Low numbers of Salmonella have also been found in nonphagocytic stromal cells of the intestinal lamina propria that are probably fibroblasts. 12 In this cell type Salmonella actively restrain their proliferation. Carrier state infections are commonly observed in human and domestic fowl following an acute phase.…”
mentioning
confidence: 99%